2017
DOI: 10.1038/s41467-017-00320-1
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide association study of classical Hodgkin lymphoma identifies key regulators of disease susceptibility

Abstract: Several susceptibility loci for classical Hodgkin lymphoma have been reported. However, much of the heritable risk is unknown. Here, we perform a meta-analysis of two existing genome-wide association studies, a new genome-wide association study, and replication totalling 5,314 cases and 16,749 controls. We identify risk loci for all classical Hodgkin lymphoma at 6q22.33 (rs9482849, P = 1.52 × 10−8) and for nodular sclerosis Hodgkin lymphoma at 3q28 (rs4459895, P = 9.43 × 10−17), 6q23.3 (rs6928977, P = 4.62 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 79 publications
(111 reference statements)
5
33
0
Order By: Relevance
“…A second independent signal was identified as a variant in DQA1*02:01 , but this was nearly perfectly correlated with the previously identified DRB1*07:01 and thus is not likely to be a novel variant. A third GWAS from the same group identified additional potential associated HLA variants that were histology subtype‐specific: for NSHL, rs9269081 mapping close to the 3′ end of HLA class II DRA, and for MCHL, rs1633096 mapping to the 3′ end of HLA‐F . Finally, rs6457715, near HLA‐DPB1, was identified by a European GWAS to reduce EBV‐positive HL risk, independent of histological subtype .…”
Section: Hodgkin Lymphomamentioning
confidence: 96%
“…A second independent signal was identified as a variant in DQA1*02:01 , but this was nearly perfectly correlated with the previously identified DRB1*07:01 and thus is not likely to be a novel variant. A third GWAS from the same group identified additional potential associated HLA variants that were histology subtype‐specific: for NSHL, rs9269081 mapping close to the 3′ end of HLA class II DRA, and for MCHL, rs1633096 mapping to the 3′ end of HLA‐F . Finally, rs6457715, near HLA‐DPB1, was identified by a European GWAS to reduce EBV‐positive HL risk, independent of histological subtype .…”
Section: Hodgkin Lymphomamentioning
confidence: 96%
“…For example, the meta-analysis of 7 GWAS studies, for a total of 5,325 HL patients and 22,423 controls (31), demonstrated that 5 new loci were significantly associated with inherited susceptibility to HL and dysfunction of the immune system, independently from patients' age or histological subtype. A similar study based on three GWAS trials identified a set of loci (with a special representation of transcription factors) significantly correlated with the risk of developing classical HL (30). In other cases, GWASs investigate possible predictive markers of drug sensitivity or tolerability to optimize pharmacological treatments in the clinical routine.…”
Section: Unsupervised Search For Targetsmentioning
confidence: 99%
“…We used GWAS data generated on 3 nonoverlapping casecontrol series of Northern European ancestry, which have been the subject of previous analyses (supplemental Tables 1 and 2, available on the Blood Web site). 11 The UK-GWAS was based on 622 cases ascertained through the Royal Marsden Hospital National Health Service Trust Family History study during 2004 to 2008, 14 and 5677 control patients from the UK Wellcome Trust Case Control Consortium 2. 15 The German-GWAS comprised 1001 cases ascertained by the German Hodgkin Study Group during 1998 to 2007, and 2092 control patients from the Heinz Nixdorf Recall study.…”
Section: Gwasmentioning
confidence: 99%
“…16 The UK-NSHLG-GWAS used 1717 cases ascertained through the National Study of Hodgkin Lymphoma Genetics (https://www.ukctg.nihr.ac.uk) from 2010 to 2013. 11 Control patients comprised 2976 cancer-free men recruited by the PRACTICAL Consortium, the UK Genetic Prostate Cancer Study (UKGPCS; age ,65 years), a study conducted through the Royal Marsden NHS Foundation Trust and Study of Epidemiology & Risk Factors in Cancer, recruited via general practitioner practices in East Anglia (2003)(2004)(2005)(2006)(2007)(2008)(2009); and 4446 cancer-free women from across the United Kingdom via the Breast Cancer Association Consortium. Details of the genotyping platform and quality control measures applied to each of the 3 GWAS have been described previously and are detailed in supplemental Tables 3 and 4.…”
Section: Gwasmentioning
confidence: 99%
See 1 more Smart Citation